2005
DOI: 10.1038/sj.gene.6364223
|View full text |Cite
|
Sign up to set email alerts
|

PDCD1: a tissue-specific susceptibility locus for inherited inflammatory disorders

Abstract: Variation in genes encoding costimulatory molecules expressed on lymphocytes has been expected to contribute to the genetic component of inflammatory disease, but only the gene encoding the inhibitory protein, CTLA-4, seems consistently to confer disease susceptibility. Studies in murine models implicate the inhibitory product of the pd1 gene, programmed death-1, in the maintenance of peripheral tolerance to self-antigens. We identify 22 single-nucleotide polymorphisms (SNPs) in the equivalent human gene, PDCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 53 publications
1
40
1
Order By: Relevance
“…8 There were also reports of association of PDCD1 with SLE phenotypes or other immune-mediated diseases that were independent of the PD1.3 SNP. 11,12,16,17 Often polymorphisms show a gradient of frequencies across Europe. These patterns of variation have been called allele frequency clines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 There were also reports of association of PDCD1 with SLE phenotypes or other immune-mediated diseases that were independent of the PD1.3 SNP. 11,12,16,17 Often polymorphisms show a gradient of frequencies across Europe. These patterns of variation have been called allele frequency clines.…”
Section: Discussionmentioning
confidence: 99%
“…In other study, SNPs different from PD1.3 were associated with RA susceptibility in British patients and with the atopic phenotype of Australian subjects. 17 Further research will be necessary to clarify the role of PDCD1 variation given the important involvement of this immunoreceptor in autoimmunity and chronic viral infections. 6,7 It can be questioned whether differences in PDCD1 variants between different populations could be related with changes in SLE prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that PD-1 gene polymorphisms are correlated with autoimmune diseases such as ankylosing spondylitis [17], rheumatoid arthritis [10], and systemic lupus erythematous [20]. Moreover PD 1.3 SNP has been reported in different autoimmune settings, including rheumatoid arthritis [14], Type I diabetes [11], Multiple sclerosis [15], Ankylosing spondylitis [16] and Allergy [17].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover PD 1.3 SNP has been reported in different autoimmune settings, including rheumatoid arthritis [14], Type I diabetes [11], Multiple sclerosis [15], Ankylosing spondylitis [16] and Allergy [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation